FROM DIGITIZED SCIENCE TO DIGITIZED SOCIETY - I. P. Smirnov (Образование и наука)
Introduction. Along with other innovations, in recent years, scientometric methods for measurement of scientists’ and research teams’ results in the scientific sphere have been widely adopted. The Russian practice of application of those methods to determine the degree of academics’ performance isn't unambiguous and eventually can have negative, destructive consequences for domestic science. In this regard, this very burning issue is required for urgent thorough public discussion by scientific community.The aim of the article is a critical analysis of the topical problems of science reform in the light of the law “On the Russian Academy of Sciences, the reorganization of state academies of sciences and amendments to certain legislative acts of theRussian Federation” (№ 253-RF, 27 September, 2013). Also, the author notes the importance of methods for evaluating the effectiveness of scholarly endeavor.Results and scientific novelty. On the example of the system of digital indicators operating in the Russian Academy of Education, formed on the basis of the requirements of the Ministry of Education and Science of the Russian Federation and Federal Agency of Scientific Organizations, it is shown that it is impossible to evaluate the scientific result objectively.It is clearly proved that the indicators used, primarily the number of publications and the citation index, in modern conditions give distorted landmarks, become a brake on science, reduce its ability to self-development. The image of scientists and whole institutions is formed on false indicators.Academic and many scientific journals have acquired a commercial nature; there is no real evaluative analysis of the manuscripts, which have been submitted into the editorial office; there is no selection according to relevance and significance of the submitted material. Real examples, provided in the article, demonstrate frequent violations of ethical principles when forming authorial collectives of publications of scholarly journals; as a consequence, artificial increase of citation indexes and x-index.In addition, the formalized digitized indicators become the basis for automatic, “fair”, according to officials, distribution of resources and material rewards for scientific research. It is highlighted that digitization of science and quantitative indicators based on grant financing can not replace basic funding of science. Grants become a task not for research, but for the result formulated by the official, on loyalty to the state management.The policy of nationalization and administration of science has led to a prolonged confrontation between the academies and the authorities. In the long term, it is possible to transfer the digitized principles of science management to the management of society as a whole.Practical significance. The author puts forward a number of recommendations and suggestions how to objectify the evaluation system of scientific research effectiveness. That would, however, require substantial restructuring of the scientific sphere itself, its denationalization and return to the principle “science should be managed by scientists”. Thus, science funding must not be focused on the basis of digitized indicators. It is necessary to withdraw the status “Higher Attestation Commission of the RF” (VAK RF) from all commercial journals, to remove state academies from their founders.